Expression of CD44 splice variants in squamous epithelia and squamous cell carcinomas of the head and neck - Herold-Mende, Christel; Seiter, Simone; Born, Ivan Antonio; Patzelt, Erik; Schupp, Michael; Zöller, Joachim E.; Bosch, Franz X.; Zöller, Margot (The journal of pathology, 1996)
Splice variants of the adhesion molecule CD44 have been described as essential for the lymphatic spread of rat tumour cells and are claimed to be involved in the metastatic spread of several human tumours. Immunohistochemistry has been used to analyse the expression pattern of CD44 standard (CD44s) and variant (CD44v) isoforms in normal and dysplastic squamous epithelia, as well as in primary and metastatic squamous cell carcinomas (SCCs), which spread predominantly by way of the lymphatic system. Frozen sections of squamous epithelia and of squamous cell carcinomas were stained with a panel of monoclonal antibodies recognizing epitopes of CD44s as well as of the variant exons v5, v6, v7, v7-v8, and v10. The stratum basale and stratum suprabasale of squamous epithelia stained with all antibodies; the stratum spinosum stained with anti-CD44v5, anti-CD44v6, anti-CD44v7-8 and anti-CD44v10; the lower layers of the stratum corneum stained with anti-CD44v5. This expression profile was seen in epithelia of the lip, the tongue, the gingiva, the hard palate, the floor of the mouth, the buccal mucosa, and the pharynx. The same pattern of expression was also noted in dysplastic epithelia, but expression of the variant exons v7, v8, and v10 was significantly downregulated in primary squamous cell carcinomas and was not detected at all in the majority of metastasis-derived specimens. Expression of CD44v5 and CD44v6, on the other hand, was mainly unaltered. Thus, epithelial cell layers representing different stages of differentiation express distinct sets of CD44 variant isoforms, where especially exons v8-v10 might be required for the maintenance of the structural integrity of squamous epithelium. Downregulation of these exons on tumour cells could indicate that they are irrelevant for tumour progression or may even hamper infiltration of surrounding tissue or of lymphatics.
Elektronische Reproduktion der Druck-Ausgabe 19. April 1999
Gesehen am 14.05.2024